Survival of Critically Ill Oncologic Patients Requiring Invasive Ventilatory Support: A Prospective Comparative Cohort Study With Nononcologic Patients - López, Rene (J Glob Oncol, 2019)
PURPOSE: Cancer is in the process of changing to become a chronic disease; therefore, an increasing number of oncologic patients (OPs) are being admitted to intensive care units (ICUs) for supportive care of disease or therapy-related complications. We compare the short- and long-term outcomes of critically ill mechanically ventilated OPs with those of their nononcologic counterparts. PATIENTS AND METHODS: We performed a prospective study of patients admitted to our ICU between October 2017 and February 2019. Demographic, physiologic, laboratory, clinical, and treatment data were obtained. The primary outcome was survival at 28 days and at the end of the follow-up period. Secondary outcomes were survival according to acute severity scoring (Acute Physiology and Chronic Health Evaluation II score), Eastern Cooperative Oncology Group (ECOG) performance status, and Charlson comorbidity index. RESULTS: A total of 1,490 patients were admitted during the study period; 358 patients (24%) were OPs, and 100 of these OPs were supported with mechanical ventilation. Seventy-three percent of OPs had an ECOG performances status of 0 or 1, and 90% had solid tumors. Reason for admission to the ICU was postoperative admission in 44 patients and neutropenic infection in 10 patients. The follow-up period was 148 days (range, 42 to 363 days). Survival at 28 days was similar between OPs and nononcologic patients and associated with the Acute Physiology and Chronic Health Evaluation II score. However, long-term survival was lower in OPs compared with nononcologic patients (52% v 76%, respectively; P < .001) and associated with poor ECOG performance status. CONCLUSION: Short-term survival of critically ill, mechanically ventilated OPs is similar to that of their nononcologic counterparts and is determined by the severity of the critical illness.